Inhibitory ability of robusta coffee bean extract against Staphylococcus epidermidis - Lister, Clarissa; Ginting, Rapael; Panggabean, Endah Ansylla; Tarigan, Ermilia Laurensya (Buletin Kedokteran & Kesehatan Prima, 2024)
Background: Treatment of infections generally uses chemical antibiotics, but chemical antibiotics have effects such as increasing toxicity to the body. The solution to overcome this problem is to use antibiotics from natural ingredients, such as coffee. Objective: This study aims to determine the effectiveness of robusta coffee bean extract (Coffea canephora) in inhibit the growth of Staphylococcus epidermidis bacteria. Methods: This research is an experimental study with a post test only control group design. There were 10 groups in this study, namely 2 control groups and 8 treatment groups. The technique used is disc diffusion to see the role of robusta coffee bean ethanol extract in inhibiting the growth of Staphylococcus epidermidis bacteria. The data was analyzed using the Mann-Whitney test to determine the difference between treatments. Results: The results of the Mann-Whitney test showed that there were differences in the average inhibition zone of Robusta coffee bean extract and the inhibitory power at each concentration (p<0.05). The concentration that has the highest inhibition is the concentration of 500 mg/ml. Conclusion: It can be said that there is an effectiveness of robusta coffee bean extract in reducing Staphylococcus epidermidis bacteria because the specified concentration inhibition zone is obtained.